Comparative Clinical Study on the Effect of Sarjarasadi Malahara and Vipadikahara Ghrita-Taila in the Management of Vipadika (AYUSHDHARA, 2022)
Vipadika is one among the several types of skin disorders elaborated by Ayurveda. A randomized open comparative clinical study was done on 30 no of patients diagnosed as Vipadika at V.Y.D.S. Ayurveda Mahavidyalaya, Khurja. They were divided into two groups. In Trial group (TG) 15 cases treated with Sarjarasadi Malahara and in Control group (CG) 15 cases treated with Vipadikahara Ghrita-taila.The percentage of improvement was 95.13%, 96.79%, 96.15%, 86.68%, 95.13%, 94.57% in Vipadikahara Ghrita-taila and 87.19%, 84.39%, 73.53%, 90.91%, 87.19%, 76.65% in Sarjarasadi Malahara in respect to Panipaada Sphutanam (cracks of hands and feet), Vedana (pain), Kandu (itching), Daha (burning sensation), total number of cracks, total length of cracks. The statistical adjudication with suitable parameters shows that both drugs were extremely/very significant on subjective and objective parameters among both groups. The overall clinical effect of therapy shows that, 73.33% and 33.33% patients get maximum improvement, 26.67% and 53.33% get moderate improvement, 0% and 6.67% get mild improvement with Vipadikahara Ghrita-taila and Sarjarasadi Malahara respectfully.Defining to the benefits assessed both the drugs were found capable to enforce relief, but based on percentage of improvement and overall result, it can be concluded that Vipadikahara Ghrita-taila was more effective than Sarjarasadi Malahara